4-H Florida-Friendly Landscaping™ Leader Guide: 4H411, 9/2021 - Pipoly, John; Toomey, Angelina; Hensley, Sarah; Momol, Esen; Marvin, Jennifer W.; Perez, Kelly (EDIS, 2021)
Florida-Friendly LandscapingTM (FFL) protects natural resources through water conservation, waste and nonpoint source pollution reduction, erosion prevention, and creation of wildlife-sustaining habitats by implementing science-based landscaping practices. 4-H Florida-Friendly LandscapingTM Curriculum fosters environmental stewardship among youth and allows them to engage in conserving water, soil, and vegetation resources from an early age. This curriculum addresses Florida’s unique environment and may be used alone or as a supplement to the 4-H Junior Master Gardener curriculum. Through 4-H Florida-Friendly LandscapingTM Curriculum, youth will learn nine basic principles of FFL, including water, soil, and vegetation conservation through landscape and gardening activities. This curriculum targets youth in grades 6 to 8 (ages 10 to 14) and contains both in-classroom and home activities that allow youth to understand and engage the world around them, thereby helping them gain life skills in the areas of Head, Heart, Hands, and Health. All volunteers and instructors utilizing this resource should work with their local 4-H Extension Agent to appropriately enroll youth in 4-H in order for them to experience the full benefits of the 4-H Youth Development program and to receive credit for completion of a 4-H project. Leader Guide; https://edis.ifas.ufl.edu/4h411